Exploring Perception of the Latest Covid-19 Official Educational Measures amongst Algerian Secondary School Teachers - Benamor, Youcef; Adil, Amina Assila (Technium Social Sciences Journal, 2022)
Taking novel and less killing identities, Covid-19 has created havoc in education systems worldwide and Algeria was no exception. The Algerian authorities and education policymakers consequently found themselves obliged to take measures necessary to adapt schooling and learning environments to this health crisis. Hence, this study aimed to unravel secondary school teachers’ perceptions of the adopted Covid-19 educational measures so as to 1) explore the changes they brought about into the learning environment and 2) investigate their effects on the learning process. To this end, exploratory research was conducted, opting for a mixed-method approach using document analysis and a questionnaire to which 140 teachers responded. The findings reveal that the most significant changes in the learning environment were at the level of a school setting, class size, instruction time, curricula volume, and delivery mode; all of which affected the learning process to varying degrees.